2017
DOI: 10.15537/smj.2017.3.16110
|View full text |Cite
|
Sign up to set email alerts
|

High preoperative serum ferritin predicted poor prognosis in non-metastatic colorectal cancer

Abstract: Objectives:To validate the prognostic significance of preoperative serum iron metabolism parameters in non-metastatic colorectal cancer patients treated with curative resection.Methods:We conducted a prospective cohort study in the Department of Surgical Oncology, WuXi 4th People’s Hospital, WuxiChina, between March 2010 and September 2013. The relationships of serum iron metabolism parameters with other variables were examined. The prognostic significance was evaluated using the Kaplan Meier curve and Cox pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“… 8 10 14–16 Previous studies have demonstrated that high SF is associated with worse prognosis in lung cancer, colorectal cancer, PC and peripheral T-cell lymphoma. 10 17–19 However, the prognostic role of SF in HCC is controversial. 20 21 …”
Section: Introductionmentioning
confidence: 99%
“… 8 10 14–16 Previous studies have demonstrated that high SF is associated with worse prognosis in lung cancer, colorectal cancer, PC and peripheral T-cell lymphoma. 10 17–19 However, the prognostic role of SF in HCC is controversial. 20 21 …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there is a higher degree of transferrin serum iron saturation [55,57,58]. Therefore, the determination of the level of latent ironbinding capacity or ferritin concentration is a more accurate indicator of iron deficiency in cancer than the content of iron in the blood serum [58][59][60][61].…”
Section: Ironmentioning
confidence: 99%
“…Hepcidin in turn blocks iron release from macrophages, increases ferritin levels, and lowers transferrin saturation levels [ 30 ]. Ferritin, measured in routine blood examinations, is the primary iron-binding protein that exists both intracellularly and extracellularly [ 31 ]. Evidence has indicated that ferritin may play a role in cancer proliferation and immunosuppression, as well as therapeutic resistance [ 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both studies showed that high ferritin levels were associated with poor survival in both resectable CRC [ 31 ] and mCRCs [ 43 ]. It is worth noting that when stratified by TNM stages, ferritin levels remained statistically significant with only stage III patients [ 31 ]. Haptoglobin, on the other hand, was also associated with poor survival.…”
Section: Literature Reviewmentioning
confidence: 99%